2020
DOI: 10.3390/soilsystems4030047
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cathode Material and Its Size on the Abundance of Nitrogen Removal Functional Genes in Microcosms of Integrated Bioelectrochemical-Wetland Systems

Abstract: Constructed wetland-microbial electrochemical snorkel (CW-MES) systems, which are short-circuited microbial fuel cells (MFC), have emerged as a novel tool for wastewater management, although the system mechanisms are insufficiently studied in process-based or environmental contexts. Based on quantitative polymerase chain reaction assays, we assessed the prevalence of different nitrogen removal processes for treating nitrate-rich waters with varying cathode materials (stainless steel, graphite felt, and copper)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…Microbes possessing nirK genes are naturally in high abundances in nature, and therefore, their presence on the WE should not always be correlated to any specific activity (Lam and Kuypers, 2011;Hallin et al, 2018). The previous study on the microbial electrochemical systems also showed increased abundances of nirS and nosZI gene-harboring microbes (Gadegaonkar et al, 2020), supporting our results and indicating probable complete denitrification.…”
Section: Abundance Of Nitrification Genes On the Electrodessupporting
confidence: 87%
“…Microbes possessing nirK genes are naturally in high abundances in nature, and therefore, their presence on the WE should not always be correlated to any specific activity (Lam and Kuypers, 2011;Hallin et al, 2018). The previous study on the microbial electrochemical systems also showed increased abundances of nirS and nosZI gene-harboring microbes (Gadegaonkar et al, 2020), supporting our results and indicating probable complete denitrification.…”
Section: Abundance Of Nitrification Genes On the Electrodessupporting
confidence: 87%
“…However, this method may cause secondary contamination. Alternatively, studies have shown that a larger electrode size increases the conductivity of BES (Gadegaonkar et al, 2020). Therefore, the applied liquid electrolyte and dosage should be selected rationally according to the actual situation.…”
Section: Optimization Of Electrical Conductivitymentioning
confidence: 99%